"The Childhood Shows the Man":. Issue 2 (14th April 2015) - Racine, Karen
<x content-type="archive" xml:space="preserve">Abstract</x> In his epic poem Paradise Regained (1671), John Milton has Satan observe that "The childhood shows the man/As morning shows the day/ Be famous then/ By wisdom. As the empire must extend/ So let extend thy mind o'er all the world." As parents and as patriots, the leaders of Latin America's revolutions for independence wanted bright futures for both their children and their young nations. In many ways, the goals they set for each were the same: enhanced commercial opportunities, a political arena marked by greater freedom of speech and open debate, the rule of law, government with a strong moral center in which the privileged members of society had a responsibility to set a good example, and, perhaps most cherished of all, access to modern scientific and secular education. As figurative parents of emerging nations, and as biological parents of impressionable youth, these creole founding fathers wished to instill useful patriotic values in their national and personal families alike. Bridging the Enlightenment and Romantic eras, Latin American independence rhetoric blurred the distinction between nation-building and paternity, indicating that its leaders saw themselves as parents in more than one sense.